Generative AI and Argument Creativity - Vigeant, Louise (Informal Logic)

(untitled) (Informal Logic, 2024)
Generative AI appears to threaten argument creativity. Because of its capacity to generate coherent texts, individuals are likely to integrate its ideas, and not their own, into arguments, thereby reducing their creative contribution. This article argues that this view is mistaken—it rests on a misunderstanding of the nature of creativity. Within arguments, creative and critical thinking cannot be separated. Because creativity is enmeshed with skills such as analysis and evaluation, the use of generative AI in the construction of arguments, especially in the role as universal audience, has the potential to heighten, not diminish argument creativity.